MENGANALISIS MAKNA SABAT DAN PENERAPANNYA DALAM KONTEKS PERJANJIAN LAMA - Hia, Vivian Vian (Sekolah Tinggi Teologi Hagiasmos Mission, 2024)
The Sabbath as a moral principle and symbol of God's covenant with His people. It emphasises the importance of the sabbath in fostering a harmonious relationship with God and finding peace and purpose in life. Obedience in observing the sabbath shows the quality of an individual's life, which is to have hope for the salvation of the soul. The research method used in this research is literature and library studies. In this method the author takes several general steps such as systematically identifying theories, identifying books, journals, Bible verses and other publications that are relevant to the topic of discussion. The result of this study is that the sabbath has a sacred and important meaning in a religious context, as a day of rest and reflection that allows individuals to strengthen their relationship with God and with the community of faith. By observing the sabbath, individuals can find a more meaningful purpose in life, because individuals who crave peace and tranquility will find their purpose in a good relationship with God through sincere worship.